A cognitive-stylistic study of deixis and deictic shifting in Iris Murdoch’s The Bell - Mohammad Ghaffary; Seyed Mohammad Hosseini; Mohadesse Khosravi (نشریه پژوهش‌های زبان‌شناسی)
In cognitive stylistics, “deixis” is deemed one of the core linguistic elements through which both the physical and ideological stances of the participants in fictional narratives, namely the narrator and the character(-focalizer)s, are demonstrated. This study aims at investigating the cognitive functions of the different kinds of deixis, i.e., perceptual, spatial, temporal, social, textual, and compositional deixis, in The Bell (1958), a critically acclaimed novel by the British philosopher and novelist Iris Murdoch. Because of its special narrative discourse, in particular the use of variable internal focalization, Murdoch’s novel proves to be a proper case for exploring how deixis impacts upon the (implied) reader’s cognition of the story. Thus, utilizing a descriptive-analytic method, the present research examines the text worlds and mind styles shaped in this novel through various kinds of deixis, among other textual elements, and explores the relationship between these text worlds and the way they inform the reading process. To achieve this goal, this qualitative study draws upon the cognitive deixis theory to examine selected extracts from Dora Greenfield’s and Toby Gashe’s discourses in this novel, as two of the major character-focalizers. The findings suggest that deictic expressions serve a significant function in appreciating the characterization of the fictional personages, their relations, and consequently the narrative’s overall theme, thereby affecting and somehow directing the reading process. This mainly occurs through the reader’s cognitive pushes and pops in and out of the different layers of the narrative discourse as well as projecting the narrator’s and character-focalizers’ text worlds or deictic fields and constantly shifting among them. By foregrounding the role of deixis in narration, this study carries significant implications for cognitive stylistics of prose fictional narratives, providing a deeper appreciation of the relationships between characters and between characters and fictional settings in such texts.